PENGARUH PENGEMBANGAN KARIR DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI PADA BPJS KESEHATAN KEDEPUTIAN WILAYAH SUMBAGTENG JAMBI - Rika Senja Pratama; Machasin Machasin; Ando Fahda Aulia (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study aims to analysis the effect of career development and leadership on job satisfaction. To analyze the effect of career development and leadership on performance. To analyze the effect of job satisfaction on performance. And to analyze the effect of career development and leadership on performance through job satisfaction. The population in this study were all employees who worked at the BPJS Kesehatan Deputy for the Jambi Central Sumbagteng Region which supervise 11 branch offices with total employee of 497 people in 2021. Sample used on this research were construct of 222 respondents. The data used in this study were primary data and secondary data, while the primary data collected using a questionnaire. Then, collected data were analysis using path analysis. The results showed that career development had an effect on job satisfaction. Leadership has a significant effect on job satisfaction. Career development has a significant effect on employee performance. Leadership has a positive and significant effect on employee performance. Job satisfaction has a positive and significant effect on employee performance. Career development has a positive and significant effect on employee performance through job satisfaction. Leadership has a positive and significant effect on employee performance through job satisfaction.